2007
DOI: 10.1194/jlr.m700335-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of demography, diet, lifestyle, and serum lipid levels between the Guangxi Bai Ku Yao and Han populations

Abstract: Bai Ku Yao is an isolated subgroup of the Yao minority in China. Little is known about dyslipidemia in this population. The aim of this study was to compare the effects of demography, diet, and lifestyle on serum lipid levels between the Bai Ku Yao and Han populations. A total of 1,170 subjects of Bai Ku Yao and 1,173 subjects of Han Chinese aged 15-89 years were surveyed by a stratified randomized cluster sampling. The levels of total cholesterol, high density lipoprotein cholesterol, low density lipoprotein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
138
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(149 citation statements)
references
References 52 publications
10
138
0
1
Order By: Relevance
“…Even in those who reported that they were taking treatment for dyslipidemia, only 37.8% had their serum lipids controlled. The mean serum TC, LDL-C and TG in China have increased rapidly in the last decade 4,14,15) . Findings from CNHS 2002 4,9) showed that the mean levels of TC, LDL-C and TG were 3.81 mmol/L (147.1 mg/dL), 2.12 mmol/L (81.9 mg/dL) and 1.10 mmol/L (97.3 mg/dL), respectively, which were relatively low; however, the corresponding mean levels observed in the current study were 5.05 mmol/L (195.0 mg/dL), 3.27 mmol/L (126.3 mg/dL) and 1.53 mmol/L (135.4 mg/dL), respectively, which suggested that the mean serum TC, LDL-C and TG in Beijing is coming close to those in developed countries, such as Australasia, North America, and western Europe 16,17) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in those who reported that they were taking treatment for dyslipidemia, only 37.8% had their serum lipids controlled. The mean serum TC, LDL-C and TG in China have increased rapidly in the last decade 4,14,15) . Findings from CNHS 2002 4,9) showed that the mean levels of TC, LDL-C and TG were 3.81 mmol/L (147.1 mg/dL), 2.12 mmol/L (81.9 mg/dL) and 1.10 mmol/L (97.3 mg/dL), respectively, which were relatively low; however, the corresponding mean levels observed in the current study were 5.05 mmol/L (195.0 mg/dL), 3.27 mmol/L (126.3 mg/dL) and 1.53 mmol/L (135.4 mg/dL), respectively, which suggested that the mean serum TC, LDL-C and TG in Beijing is coming close to those in developed countries, such as Australasia, North America, and western Europe 16,17) .…”
Section: Discussionmentioning
confidence: 99%
“…A few regional studies have examined the prevalence of dyslipidemia in Chinese populations recently 5,14,15) , but none of these studies reported the dyslipidemia prevalence according to the latest Chinese criteria 9) . Based on the new criteria in China, we report here the prevalence of dyslipidemia among adults in Beijing using data obtained in 2008.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 645 subjects of Bai Ku Yao who reside in Lihu and Baxu villages in Nandan County, Guangxi Zhuang Autonomous Region, People's Republic of China were randomly selected from our previous stratified randomized cluster samples [38,39]. The ages of the subjects ranged from 15 to 85 years, with an average age of 40.25 ± 15.28 years.…”
Section: Methodsmentioning
confidence: 99%
“…The subjects accounted for 2.15% of total Bai Ku Yao population. During the same period, a total of 638 people of Han Chinese who reside in the same villages were also randomly selected from our previous stratified randomized cluster samples [38,39]. The mean age of the subjects was 40.53 ± 15.54 years (range 15 to 82).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation